The Interface Approach - Eva Gerharz (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2018)
The interface approach is especially well suited to understanding the specific conditions and processes in development cooperation. Therefore, it has been mainly adopted in development studies, particularly in the field of development sociology. In order to gain an understanding of this approach and the theories behind it, the first part of this paper introduces the essential theoretical premises and their methodological significance. In the second part, a case from the author's fieldwork in Northern Sri Lanka is used to illustrate how a research design can be developed using the interface approach, and how one might analyse the collected data.
Keywords: 320